(untitled) (INNOVATIVE ECONOMY, 2021)
Pererva I.M. FUNCTIONS AND PRINCIPLES OF STANDARDIZATION OF INNOVATIVE LABOUR FOR IT INDUSTRY PROJECTS Purpose. The aim of the article is the research of modern trends in labour rationing in the IT industry; determination of the functions of standardization of innovative labour of IT specialists at three levels of management ‒ macro-, meso- (the level of the IT industry) and micro- (the level of the enterprise of the IT industry); substantiation of the principles of standardization of innovative work in the IT industry. Methodology of research. The method of logical generalization and office research was used to substantiate the functions, features, principles of standardization of innovative work in the IT industry, and the graphic method was used to visualize the presented results. Results. Current trends are considered and the main problems associated with the IT industry are explored to achieve this goal. Based on the generalization of theoretical provisions on the rationing of innovative work of IT professionals at the macro, meso, micro-economic levels, the main functions of rationing of innovative work at these levels are determined. The principles of rationing of innovative work in the IT industry are substantiated on the basis of their combination into three groups: features of rationing of innovative work, features of work of IT specialists and principles of labour rationing with separation of general and specific. Originality. The list of general and specific principles of rationing of innovative work in the IT industry is substantiated, which, unlike the existing ones, takes into account the peculiarities of rationing of innovative work of IT specialists, which allows to determine the role of innovative work in the development of an innovative model of employment and changing the structure of this model in the labour market. Practical value. Rationalization of labour processes based on innovative work can be ensured in the case of using an effective management tool, which is rationing. Generalized theoretical provisions on the functions of standardization of innovative work at different levels, sound principles of standardization of innovative work in the IT industry will help increase the validity of norms and standards of time for IT workers and enhance innovative work of employees in the IT industry. Key words: innovations, innovative work, IT industry, rationing of innovative work, functions and principles of labour rationing.